Behavioral responses during sickness in amphibians and reptiles: Concepts, experimental design, and implications for field studies - Cabanzo-Olarte, Laura Camila; Cardoso Bícego, Kênia [UNESP]; Navas Iannini, Carlos Arturo (Elsevier, 2024)
In ectothermic vertebrates, behavioral fever, where an individual actively seeks warmer areas, seems to be a primary response to pathogens. This is considered a broad and evolutionarily conserved response among vertebrates. Recent population declines in amphibians are associated with an increase of infectious disease driven largely by climate change, habitat degradation, and pollution. Immediate action through research is required to better understand and inform conservation efforts. The literature available, does not provide unifying concepts that can guide adequate experimental protocols and interpretation of data, especially when studying animals in the field. The aim of this review is to promote common understanding of terminology and facilitating improved comprehension and application of key concepts about the occurrence of both sickness behavior or behavioral fever in ectothermic vertebrates. We start with a conceptual synthesis of sickness behavior and behavioral fever, with examples in different taxa. Through this discussion we present possible paths to standardize terminology, starting from original use in endothermic tetrapods which was expanded to ectothermic vertebrates, particularly amphibians and reptiles. This conceptual expansion from humans (endothermic vertebrates) and then to ectothermic counterparts, gravitates around the concept of ‘normality'. Thus, following this discussion, we highlight caveats with experimental protocols and state the need of a reference value considered normal (RVCN), which is different from experimental control and make recommendations regarding experimental procedures and stress the value of detailed documentation of behavioral responses. We also propose some future directions that could enhance interaction among disciplines, emphasizing relationships at different levels of biological organization. This is crucial given the increasing convergence of fields such as thermal physiology, immunology, and animal behavior due to emerging diseases and other global crises impacting biodiversity.
Keywords: Amphibian; Disease; Fever; Squamata; Thermoregulation